PELATIHAN PITCH DECK ALA KAWASAKI RULE UNTUK SISWA SMAS SANTO YOSEPH DENPASAR - Eka Grana Aristyana Dewi; Desak Putu Nitya Dewi (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
This community service activity was carried out to improve students' abilities in product presentation for entrepreneurship, in line with the Merdeka Belajar Curriculum. The method used in this training involves designing a pitch deck according to the Kawasaki Rule and presenting the product (pitching). The result of this community service activity is a pitch deck presentation video for a business product that has been designed and uploaded to YouTube. From the training activities and the outputs produced, students demonstrated that this training and practice improved their abilities in presenting business products, as measured by the pitching results and pitch decks created based on an analytic assessment rubric. The assessment rubric consists of 2 categories (pitching and pitch deck) with a total of 7 indicators, namely duration, content, delivery method, slides, digital media, cohesion, and language use.